2015
DOI: 10.1016/j.ajpath.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Specific Lipopolysaccharide Serotypes Induce Differential Maternal and Neonatal Inflammatory Responses in a Murine Model of Preterm Labor

Abstract: Intrauterine inflammation is recognized as a key mediator of both normal and preterm birth but is also associated with neonatal neurological injury. Lipopolysaccharide (LPS) is often used to stimulate inflammatory pathways in animal models of infection/inflammation-induced preterm labor; however, inconsistencies in maternal and neonatal responses to LPS are frequently reported. We hypothesized that LPS serotype-specific responses may account for a portion of these inconsistencies. Four different Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 56 publications
(42 reference statements)
2
47
0
Order By: Relevance
“…We and others (11) hypothesize that the placental inflammation during ZIKV infection may contribute significantly to adverse perinatal outcomes, and should be considered in therapeutic approaches for ZIKV and other infections that cause congenital defects during pregnancy. The maternal inflammatory response represents an environmental factor that is known to increase the risk for childhood and developmental diseases (51,52), such as autism spectrum disorders, schizophrenia, learning disabilities, as well as cognitive and motor deficits (53)(54)(55). Although ZIKV infection has direct effects on fetal tissues, we show that placental inflammation is also a major contributor to adverse perinatal outcomes following in utero ZIKV infection.…”
Section: Discussionmentioning
confidence: 67%
“…We and others (11) hypothesize that the placental inflammation during ZIKV infection may contribute significantly to adverse perinatal outcomes, and should be considered in therapeutic approaches for ZIKV and other infections that cause congenital defects during pregnancy. The maternal inflammatory response represents an environmental factor that is known to increase the risk for childhood and developmental diseases (51,52), such as autism spectrum disorders, schizophrenia, learning disabilities, as well as cognitive and motor deficits (53)(54)(55). Although ZIKV infection has direct effects on fetal tissues, we show that placental inflammation is also a major contributor to adverse perinatal outcomes following in utero ZIKV infection.…”
Section: Discussionmentioning
confidence: 67%
“…However, many research groups use different LPS serotypes or LPS from different bacteria and many of them do not specify LPS serotype. It has been shown that LPS substructures could modulate its endotoxic properties, possibly by different interactions of the LPS molecule with the TLR4 receptor complex, leading to different activation of subsequent inflammatory pathways [38,39]. This is supported by studies which have found that structural differences in O-antigen of LPS molecule are able to modulate its recognition and phagocytosis by macrophages [40,41].…”
Section: Discussionmentioning
confidence: 92%
“…Growing evidence supports the notion that inflammatory responses triggered by LPS vary among serotypes. For instance, in a murine model of infection-induced preterm labor, four different E. coli LPS serotypes yielded highly variable outcomes (32). Our data suggest that subtle changes in the sugar composition of the O-antigen can impact NET release in response to LPS.…”
Section: Discussionmentioning
confidence: 99%